Multicriterial synthesis of the control law for a semi-active spatial model of the vehicle suspension - Genov, Julian (IOP conference series. Materials Science and Engineering, 2019)
This article explores the task for the multicriterial synthesis of the control-law from the type Linear Quadratic Regulator (LQR), for a semi-active vehicle suspension. It is consists of obtaining the optimal compromise between the requirements for sufficient ride comfort and vehicle stability on the road pavement. The relevant object-functions are defined. It is proposed an algorithm for a multicriterial hierarchical approach for identifying in the Pareto's set of solutions, this solution that realizes the optimal compromise in the sense of John Nash's sustained strategy from the antagonistic games theory. Based on this approach, a new algorithm for the synthesis of LQR is proposed, combined with a compensator, in which the weight matrices being the subject of optimization. This synthesis was applied for a spatial model of a semi-active suspension of a vehicle.